Adherence to ruxolitinib, an oral JAK1/2 inhibitor, in patients with myelofibrosis: interim analysis from an Italian, prospective cohort study (ROMEI). Issue 1 (2nd January 2022) - Guglielmelli, Paola; Palandri, Francesca; Selleri, Carmine; Cilloni, Daniela; Mendicino, Francesco; Mazza, Patrizio; Pastore, Domenico; Palumbo, Giuseppe A.; Santoro, Marco; Pavone, Vincenzo; Impera, Stefana; Morelli, Mara; et al.
Abstract: ROMEI, a prospective, observational study in patients with myelofibrosis receiving the oral JAK1/2 inhibitor ruxolitinib in real-world practice, assesses treatment adherence based on the 8-item Morisky Medication Adherence Scale (MMAS-8). Here, we present MMAS-8 results at week 24. Overall, 101 of 188 evaluable patients completed the questionnaire at every visit (full completers). Mean (±standard deviation) total MMAS-8 scores remained stable from week 4 to week 24 in the overall population (7.54 ± 0.77 and 7.67 ± 0.70, respectively) and full completers (7.53 ± 0.79 and 7.67 ± 0.73, respectively). Rates of low (MMAS-8 ˂6) or medium (MMAS-8 ≥ 6 to ˂8) adherence were 25–40% and 26–36%, respectively. Fifty-five full completers (54%) reported ≥1 change in adherence category (improvement and/or worsening), most of which were associated with unintentional behavior. The data suggest that one-third of patients receiving ruxolitinib may be undertreated due to non-adherence, potentially undermining disease control, and indicate a need for better interventions addressing noncompliance to oral therapies.